Application of the Holland RIASEC Model to Support Career Development - Berlian Tiara Tsani; Rosatyani Puspita Adiati (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This research aims to assess and evaluate the suitability of a PT X employee’s interests, potential, and skills for their current position. Additionally, it seeks to provide recommendations for appropriate career development. The methods used in this study include a comprehensive individual assessment approach, incorporating psychological tests, the RIASEC model, and interviews. The results indicate that the subject's interests align with the Realistic and Conventional types, making them suitable for positions such as Junior Compensation and Benefit Staff and Junior Human Capital Information System Staff. Furthermore, the findings show that the subject possesses cognitive abilities and skills that support analytical and administrative work. The implications of this research include recommending the subject for one or both positions while providing career development strategies such as training, job expansion, and mentoring. Additionally, obtaining assessment results and counseling feedback is expected to enhance employee motivation, job satisfaction, and commitment to the company. This research contributes to career development strategies that align with both organizational and individual needs. Penelitian ini bertujuan dalam membantu dan mengevaluasi kesesuaian minat, potensi dan keterampilan yang dimiliki oleh seorang karyawan PT. X terhadap jabatannya. Selain itu membantu memberikan rekomendasi dalam pengembangan karier yang tepat. Metode yang digunakan penelitian ini meliputi pendekatan asesmen individu komprehensif, berupa Tes Psikologi, RIASEC, dan Wawancara. Hasil penelitian menunjukkan adanya kesesuaian minat subjek yaitu tipe Realistic dan Conventional pada posisi jabatan sebagai Junior Staf Compensation dan Benefit maupun Junior Staf Sistem Informasi Human Capital. Selain itu hasil menunjukkan subjek memiliki kemampuan kognitif dan keterampilan yang mendukung untuk menjalankan pekerjaan yang bersifat analitis dan administrative. Implikasi penelitian ini adalah merekomendasikan penempatan subjek pada salah satu atau kedua posisi jabatan tersebut, disertai dengan pemberian rekomendasi pengembangan karier seperti training, perluasan pekerjaan dan mentoring kepada subjek. Perolehan hasil asesmen dan feedback konseling juga diharapkan meningkatkan motivasi, kepuasan kerja dan komitmen karyawan terhadap perusahaan. Sehingga penelitian ini berkontribusi terhadap strategi pengembangan karier yang sesuai dengan kebutuhan perusahaan dan individu.